The Potential Role of Dietary Platelet-Activating Factor Inhibitors in Cancer Prevention and Treatment. Issue 1 (5th February 2019) - Lordan, Ronan; Tsoupras, Alexandros; Zabetakis, Ioannis
ABSTRACT: Cancer is the second leading cause of mortality worldwide. The role of unresolved inflammation in cancer progression and metastasis is well established. Platelet-activating factor (PAF) is a key proinflammatory mediator in the initiation and progression of cancer. Evidence suggests that PAF is integral to suppression of the immune system and promotion of metastasis and tumor growth by altering local angiogenic and cytokine networks. Interactions between PAF and its receptor may have a role in various digestive, skin, and hormone-dependent cancers. Diet plays a critical role in the prevention of cancer and its treatment. Research indicates that the Mediterranean diet may reduce the incidence of several cancers in which dietary PAF inhibitors have a role. Dietary PAF inhibitors such as polar lipids have demonstrated inhibitory effects against the physiological actions of PAF in cancer and other chronic inflammatory conditions in vitro and in vivo. In addition, experimental models of radiotherapy and chemotherapy demonstrate that inhibition of PAF as adjuvant therapy may lead to more favorable outcomes. Although promising, there is limited evidence on the potential benefits of dietary PAF inhibitors on cancer prevention or treatment. Therefore, further extensive research is required to assess the effects of various dietary factors and PAF inhibitors and to elucidate the mechanisms in prevention of cancer progression and metastasis at a molecular level.